Falsification or falsification? : A critique of Popper's misunderstanding of Marx - Herrera Rodríguez, Omar S. (2025)
I show in this work that Popper's criticism in the book The Open Society and its Enemies about Marx's Method is both false in relation to the work of the German nineteenth-century thinker and inconsistent in the way that Popper presents his criticism. Thus, I propose that Marx's Popperian critique deserves to be dismissed without doubt.